j/3=-4

Simple and best practice solution for j/3=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for j/3=-4 equation:



j/3=-4
We move all terms to the left:
j/3-(-4)=0
We add all the numbers together, and all the variables
j/3+4=0
We multiply all the terms by the denominator
j+4*3=0
We add all the numbers together, and all the variables
j+12=0
We move all terms containing j to the left, all other terms to the right
j=-12

See similar equations:

| 1/3t-11=64-41/3t | | 2/3t-11=64-4/1/3t | | -7(x+7)=-55 | | 3a-7=2a-5 | | 2m-1=6m01 | | 7y-5=9y-29 | | 7y-5=97-29 | | 3x=9(3+4) | | 2/9x+10=14 | | 6x=4(x+12) | | 3x+4=30x-15 | | 5a=40-3a | | 2(n-1)+4n=(3n-1 | | 9x-16x+58=90 | | 3/7=10/v | | 1.72=x^1.5 | | 37/20b=5 | | 1.72=(x)^1.5 | | 8+12x*12x-21=0 | | 48=8-2y | | 5x(2x-13)=40 | | -30-5x=-5(7x+6) | | x+4(3x)=44 | | 12*m=2500 | | F(x)=5^2+3×5+1 | | 3x2+9=4x+8 | | 2/5x60=24 | | 5x(2×-13)=40 | | 2500=12*m | | F(5)=5^2+3x+1 | | 9=8Z+1y | | 2y=1=7 |

Equations solver categories